2017
DOI: 10.1140/epjc/s10052-017-5107-z
|View full text |Cite
|
Sign up to set email alerts
|

A non-perturbative study of matter field propagators in Euclidean Yang–Mills theory in linear covariant, Curci–Ferrari and maximal Abelian gauges

Abstract: In this work, we study the propagators of matter fields within the framework of the refined GribovZwanziger theory, which takes into account the effects of the Gribov copies in the gauge-fixing quantization procedure of Yang-Mills theory. In full analogy with the pure gluon sector of the refined Gribov-Zwanziger action, a non-local long-range term in the inverse of the FaddeevPopov operator is added in the matter sector.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 89 publications
1
28
0
Order By: Relevance
“…In the Landau gauge, dealing with Gribov copies has brought non-trivial infrared effects which might be related to the confinement of gluons, see [5,[68][69][70], a fact that has raised the investigation of such effects in other gauges. In particular, the issue of the Gribov copies in the linear covariant gauges has been object of intense research in the last years, see [46,[49][50][51][52][53][54][55]. In particular, a local and BRST invariant action which takes into account the existence of Gribov copies in the linear covariant gauges was proposed in [49], within the Gribov-Zwanziger framework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Landau gauge, dealing with Gribov copies has brought non-trivial infrared effects which might be related to the confinement of gluons, see [5,[68][69][70], a fact that has raised the investigation of such effects in other gauges. In particular, the issue of the Gribov copies in the linear covariant gauges has been object of intense research in the last years, see [46,[49][50][51][52][53][54][55]. In particular, a local and BRST invariant action which takes into account the existence of Gribov copies in the linear covariant gauges was proposed in [49], within the Gribov-Zwanziger framework.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the aforementioned prescription for a BRST-invariant (R)GZ construction in the linear covariant gauges, it was established in [50] that, in great similarity with the Landau gauge, the formation of the refining condensates happens in d = 3, 4 but not in d = 2. Also, matter fields were introduced in [55] according to the prescription developed in [32], giving rise to analytic expressions for the non-perturbative propagators for scalar fields in the adjoint representation of the gauge group as well as for quarks in the fundamental representation.…”
Section: The Refined Gribov-zwanziger Action In the Linear Covarimentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as expected, it was also confirmed that different gauge invariant operators, with matching quantum numbers, can describe the same state, by looking into their mutual overlaps/mixed propagators. In particular can one also introduce gauge invariant "dressed" operators, see [18] or [19], based on the seminal work of Dirac [20], to describe the spectrum. We will not pursue this avenue here, but the proper renormalization properties of these dressed field configurations can also be studied in the continuum, next to their correlation functions, including the overlap with the here considered operators.…”
Section: Jhep10(2021)039mentioning
confidence: 99%